2022
DOI: 10.1177/02646196221139780
|View full text |Cite
|
Sign up to set email alerts
|

When one partner can no longer see: Exploring the lived experiences of romantic partners in the context of vision loss

Abstract: This qualitative descriptive study aims to explore the lived experience of the adjustment process of couples who face vision loss, investigating the impact of such loss on daily life and the adjustments and adaptations that ensue. To undertake such an exploration, the application of an occupational perspective is relevant where the meaning and purpose partners ascribe to their everyday activities can be investigated. A total of 16 couples living in Western Switzerland were interviewed between January and June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Previous research has described the impact of sight loss on couples, particularly on shared activities. This includes a need to adapt activities to enable both partners to continue to take part and a shift in responsibilities towards the sighted partner, resulting in perceived dependence and tension in some couples ( 62 ). V.I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has described the impact of sight loss on couples, particularly on shared activities. This includes a need to adapt activities to enable both partners to continue to take part and a shift in responsibilities towards the sighted partner, resulting in perceived dependence and tension in some couples ( 62 ). V.I.…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence relating to the availability of social support to adults with V.I. Findings from the Canadian Longitudinal Study on Aging (18) showed that, among adults aged 45 to 89, vision loss (having self-reported "fair" or "poor, non-existent, or blind" eyesight with glasses or lenses) was independently associated with lower availability of different types of social support, particularly in those aged [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. Social support in this study included overall support, emotional-informational support, positive interactions, as well as affectionate and tangible support.…”
Section: Introductionmentioning
confidence: 99%